Oregon Delegation officials outside of the Oregon State Building, Alaska-Yukon-Pacific Exposition, Seattle, Washington, August 6, 1908 - Nowell, Frank H., 1864-1950 (1908)
On verso of image: A.Y.P.; Oregon St. Building Caption on image: x145 Present in group: George Chamberlain PH Coll 727.28 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number